Efficacy and Safety of the GuideLiner Mother‐in‐Child Guide Catheter Extension in Percutaneous Coronary Intervention. (14th November 2016) - Sharma, Divyesh; Shah, Ashish; Osten, Mark; Ing, Douglas; Barolet, Alan; Overgaard, Christopher B.; Džavík, Vladimír; Seidelin, Peter H.
Abstract : Background: Percutaneous coronary intervention (PCI) procedures are increasingly performed on complex tortuous and heavily calcified coronary lesions. The GuideLiner® catheter (Vascular Solutions, Inc. Minneapolis, MN) is a rapid exchange guide catheter extension system. There is paucity of data about the efficacy of this device in complex PCI. Therefore, we aim to report the indications, success, and efficacy of GuideLiner use in treating complex lesion subset in the present study. Methods: We collected data from all patients in whom the GuideLiner was used to facilitate PCI between April 1, 2011 and December 31, 2014 at a tertiary referral center in Toronto, Canada. Demographic and procedural data were obtained from an institutional prospective data registry. Indications for use of the GuideLiner, and angiographic and procedural data specific to the device were also collected. Results: The GuideLiner was utilized in 307 (317 lesions) of 6105 PCI procedures performed at our institution during the study period. The mean age was 68.4 ± 11.2 years and 82% were male. The majority of lesions were types B2 or C (98%), calcified (86.3%), with proximal tortuosity (88.6%). The overall technical success rate of the GuideLiner was 88%. The procedural success rate was 98.7%. The complication rate was low (1.6%). Conclusions: Use of the GuideLiner catheter facilitated successful completion of PCI procedures in a majority of patients with complex lesions. Operators should be aware of the potential complications associated with GuideLiner use.